2013
DOI: 10.1016/j.nutres.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Soy proteins and isoflavones reduce interleukin-6 but not serum lipids in older women: a randomized controlled trial

Abstract: Soy foods contain several components, notably, isoflavones and amino acids, that may improve cardiovascular health. We evaluated the long-term effect of soy protein and/or soy isoflavones supplementation on serum lipids and inflammatory markers using a 1-year randomized, double-blind, placebo-control, clinical trial in 131 healthy ambulatory women older than 60 years. We hypothesized that soy protein, in combination with isoflavones, would have the largest positive effect on coronary heart disease risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 30 publications
3
60
2
1
Order By: Relevance
“…Interestingly, it was found that soy protein significantly decreased the level of the inflammatory maker IL-6 and that soy isoflavones tended to decrease IL-6 level. No difference was found in the inflammatory maker CRP (44). In our study, an inverse association was not found between intake of soy foods and/or soy isoflavone and inflammatory markers ( Table 2).…”
Section: The Journal Of Medical Investigation Vol 65 February 2018contrasting
confidence: 52%
“…Interestingly, it was found that soy protein significantly decreased the level of the inflammatory maker IL-6 and that soy isoflavones tended to decrease IL-6 level. No difference was found in the inflammatory maker CRP (44). In our study, an inverse association was not found between intake of soy foods and/or soy isoflavone and inflammatory markers ( Table 2).…”
Section: The Journal Of Medical Investigation Vol 65 February 2018contrasting
confidence: 52%
“…Extensive epidemiology studies (Zhuo, Melby, & Watanabe, 2004;Li, Liu, Wang, Zhao, & Feng, 2016) and animal studies (Rosier & Saes, 2006;Sbarouni, Iliodromitis, Zoga, Theodorakis, & Kremastinos, 2007) have shown that genistein can significantly decrease plasma LDL-C, TC, total triglycerides, as well as homocysteine levels, and also increase plasma HDL-C levels, which improves endothelial function and reduces the risk factors of atherosclerosis. However, others consider that soy protein and isoflavone (either alone or together) have no effect on plasma lipids or inflammatory biomarkers to prevent cardiovascular disease, even though isoflavone levels are substantially increased in blood and urine (Meyer et al, 2004;Mangano et al, 2013). We previously showed that genistein had benefits on plasma and hepatic lipid metabolism in high-fat-diet induced nonalcoholic steatohepatitis (NASH) rats through modulating the key transcription factors, including SREBP, PPAR, and AMPK (Liu, Zhong, Yin, & Jiang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials with soy protein were performed using doses of 15-56 g of protein/day [39][40][41][42]; however to date, no clinical reports have investigated rice protein intake. Consequently, in the present study, we used a smaller amount of protein, i.e., 10 g/day, to avoid potential health hazards.…”
Section: Discussionmentioning
confidence: 99%